ANALYSIS OF THE MOST UP-TO-DATE SERVER DATABASE MANAGEMENT SYSTEMS - Худайбердиев, Сахобиддин (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
Abstract. Objective. The purpose of this article is to conduct an overview and comparative analysis of the most up-to-date server database management systems, including Informix Dynamic Server, Microsoft SQL Server, Db2 Universal Database and Oracle 9i. we strive to identify the main characteristics and distinctive features of each of these DBMS, as well as to evaluate their advantages and limitations. Methods. For the analysis, we relied on available sources of information, including official documents, technical documentation, scientific articles and publications, as well as experienced users and database experts. Results. the analysis showed that each of the considered DBMS has its own advantages and disadvantages. Informix Dynamic Server stands out for a wide range of architectural features that provide high performance and scalability, but require a higher level of professionalism in administration. Microsoft SQL Server is attractive for the Windows operating system, has a developed dialect of the SQL language and a rich set of development tools, but is mainly focused on integration with other Microsoft products. Db2 Universal Database provides high performance, scalability and multiplatform, but has a complex interface and functionality. Oracle 9i is focused on use in the Internet environment, supports various hardware and software platforms, but requires highly qualified developers and administrators. Conclusion. In this paper, we considered the signs by which it is possible to analyze the advantages and disadvantages of database management systems (DBMS). During the performance analysis, the indicators of query execution speed, transaction processing and scalability of the system with an increase in data volume were considered. Data availability has also been studied, including the possibility of replication and fault tolerance of the system, special attention is paid to the functionality of the DBMS server. Keywords: database management systems, performance, scalability, data availability, server functionality, DBMS openness, development tools, administration tools, DB2, Oracle, Microsoft SQL Server, Informix, advantages, disadvantages.